Dual-effects of adsorption and photodegradation of methylene blue by tungsten-loaded titanium dioxide - -, Saepurahman; Abdullah, Mohd Azmuddin; Chong, Fai Kait (2010)

(untitled)
Surface modification of titanium dioxide (TiO2) with tungsten was carried out to increase the photocatalytic degradation of methylene blue (MB). The modified photocatalyst in dark experiment had high affinity towards MB with the amount adsorbed proportional to the tungsten loading and the highest adsorption was at 6.5 mol% tungsten loading. The adsorption isotherm study showed that the adsorption followed Langmuir model withmaximumadsorption capacity of 95.9×10−3 mmolg−1, 8-fold higher than the reported value for unmodified TiO2. Under illumination, the modified photocatalyst also enhanced the degradation of MB as compared to the unmodified one. Kinetic studies on the photocatalytic degradation of MB using linear and non-linear regression methods suggested that the degradation followed first order kinetics. The photocatalytic activity was greatly affected by the amount of tungsten loading, calcination temperature and calcination duration. The optimum synthesis condition was found at 1 mol% tungsten loading and calcination at 450 ◦C for 2 h. Using UV filter, the DRUV-Vis analysis confirmed that the enhancement of the photocatalytic activity was not due to the extension of the photoresponse into the visible region. The presence of UV portion rather enhanced the photocatalytic activity.